Embedded Selves: Co-Constructing a relationally based career workshop for rural girls - Shepard, Blythe (Canadian Journal of Counselling and Psychotherapy, 2007)
As economic, technological, and social changes transform rural areas, female youth face particular challenges in making educational/career decisions. Relationships within the community enhance and constrain future paths. Building on an earlier research study (Shepard, 2004), the co-construction of a community-based workshop with research participants is described. Workshop activities are clustered under three topic areas: knowledge of me in my local worlds; knowledge of the world of work inside and outside my community; and strengthening my future. Practical guidelines for career counsellors are provided, including the importance of developmentally appropriate experiences and contextual relevance. Workshop adaptation and extension are outlined.